Studi Tentang Cognitive Control Anak di Luar Nikah di Desa Pineleng 1 Kab. Minahasa - Tellma M. Tiwa (Peneliti.net, 2022)
The purpose of this research is to determine the cognitive control of illegitimate children in dealing with social perceptions that arise in the Pineleng 1 community, Pineleng District, Minahasa Regency. The method used in this research is a qualitative method. The subjects studied were 2 late teenagers as respondents and their status. children out of wedlock. The subject characteristics that determine the subject's status are illegitimate children and those in their late teens. The data collection methods used are 1) Observation 2) Interviews 3) Documents or archives. The results of this research show that a person's cognitive control can be or can be changed to be positive because of the presence of scars or a very gloomy past and from there he can learn from experience and He also receives help from people around him who want to help him not to get lost in sadness and use the pressure he faces as a guide to move forward and develop.